Deprescribing practices, habits and attitudes of geriatricians and geriatricians-in-training across Europe: a large web-based survey - Poelgeest, Eveline van; Seppala, Lotta J.; Lee, Jihoo M.; Bahat, Gülistan; Ilhan, Birkan; Lavan, Amanda H.; Mair, Alpana; van Marum, Rob J.; Onder, Graziano; Ryg, Jesper; Fernandes, Marília Andreia; Garfinkel, Doron; et al. (European geriatric medicine, 2022)
Aim: To explore current deprescribing attitudes and practices among geriatricians and geriatricians-in-training across Europe. Findings: Functional decline, adverse drug reactions and adherence to guidelines/checklists for managing polypharmacy were the most important reasons for deprescribing. The most important barriers for deprescribing were patients’ unwillingness, fear of negative consequences, lack of time, and poor communication between multiple prescribers. Only one in four respondents thought education in medical school had sufficiently prepared them for deprescribing in clinical practice. Message: There is a need for improved inter-professional communication, better education and evidence-based recommendations to improve future person-centered prescribing and resultant deprescribing practices.